Summer cover crops fix nitrogen, increase crop yield and improve soil-crop relationships - Blanco-Canqui, Humberto; Claassen, M. M.; Presley, DeAnn R. (My University, 2012)
Impact of cover crops (CCs) on winter wheat [Triticum aestivum (L.)] and grain sorghum [Sorghum bicolor (L.) yields is not well understood. We assessed crop yield and its relationships with CC-induced changes in soil properties for a 15-yr CC experiment in wheat-sorghum rotation at 0, 33, 66, and 100 kg ha[superscript]-1 of N application in south central Kansas. Hairy vetch (Vicia villosa Roth) was used as a winter CC from 1995 to 2000, while sunn hemp (SH; Crotalaria juncea L.) and late-maturing soybean (LMS; Glycine max L.) were used as summer CCs in no-till from 2002 to 2008. Summer CCs increased crop yields particularly at low rates of N application. At 0 kg N ha[superscript]-1, SH increased sorghum yield by 1.18 to 1.54 times, while wheat yield increased by 1.60 times in the first year (2004) after CC establishment relative to non-CC plots. At 66 kg N ha[superscript]-1, SH had no effects on sorghum yield, but it increased wheat yield in three of four years. Cover crops increased near-surface soil total N pool by 270 kg ha[superscript]-1. Crop yield increased with the CC-induced decrease in soil maximum compactibility (soil’s susceptibility to compaction) and soil temperature, and increase in soil aggregate stability, soil organic C (SOC) and total N concentration, and soil water content, particularly at 0 kg N ha-1. Principal component analysis (PCA) selected soil compactibility and total N as the best yield predictors. Inclusion of summer legume CCs in no-till fixes N, increases crop yield and improves soil-crop relationships.
Citation: Blanco-Canqui, H., Claassen, M. M., & Presley, D. R. (2012). Summer cover crops fix nitrogen, increase crop yield and improve soil-crop relationships. Agronomy Journal, 104(1), 137-147.
Keywords: Cover crops; Winter wheat; Grain sorghum; Hairy vetch; Sunn hemp; Late-maturing soybean; Soil-crop relationship; Nitrogen fixing